Creating a digital medical illustration. (2nd April 2016) - Culley, Joanna
Abstract: This paper covers the steps required to complete a medical illustration in a digital format using Adobe Illustrator and Photoshop. The project example is the surgical procedure for the release of the glenohumeral joint for the condition known as 'frozen shoulder'. The purpose is to demonstrate one method which an artist can use within digital media to create a colour illustration such as the release of the glenohumeral joint. Included is a general overview as how to deal with the administration of a medical illustration commission through the experience of a professional freelance artist.